Dreams : mind movies of the night - Tull, Mary Herd (Millbrook Press, 2000)
Examines, in a question and answer format, the scientific and cultural aspects of dreams, including such topics as the physiological reasons for dreams, the connection between dreams and religion, and the dream life of animals.